2020
DOI: 10.1016/j.jpeds.2020.05.051
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Epidemiology of Pediatric Pulmonary Arterial Hypertension

Abstract: Objective: To describe the prevalence of pulmonary arterial hypertension (PAH) associated gene mutations, and other genetic characteristics in a national cohort of children with PAH from the Dutch National registry and to explore genotype-phenotype correlations and outcome. Study design: Seventy children diagnosed with idiopathic PAH (IPAH), heritable PAH (HPAH), PAH associated with congenital heart disease (CHD) with coincidental shunt (PAH-CHD group 3), PAH after closure of a cardiac shunt (PAH-CHD group 4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 55 publications
0
27
0
5
Order By: Relevance
“…BMPR1B , CAV1 , GDF2 , KCNK3 and KDR/BMP9 were identified in one to four cases each, accounting for <1% for each gene. In addition to autosomal dominant inheritance, recessively inherited EIF2AK4 variants have been identified in 1–3% of children in European and Chinese cohorts [ 31 , 45 , 46 ]. In addition, a rare occurrence of recessively inherited GDF2 variants has been reported for a 3-year-old boy with right heart failure [ 47 ].…”
Section: Genetics Of Pediatric Pah—current Knowledgementioning
confidence: 99%
“…BMPR1B , CAV1 , GDF2 , KCNK3 and KDR/BMP9 were identified in one to four cases each, accounting for <1% for each gene. In addition to autosomal dominant inheritance, recessively inherited EIF2AK4 variants have been identified in 1–3% of children in European and Chinese cohorts [ 31 , 45 , 46 ]. In addition, a rare occurrence of recessively inherited GDF2 variants has been reported for a 3-year-old boy with right heart failure [ 47 ].…”
Section: Genetics Of Pediatric Pah—current Knowledgementioning
confidence: 99%
“…Clinical diagnoses were established by PAH specialists in accordance with the classification of the World Symposium on Pulmonary Hypertension [26]. All patients previously underwent conventional genetic screening for BMPR2, ACVRL1 and ENG, and were found to be mutation-negative [16,27]. Following pedigree analysis and clinical examination, patients were classified as having either idiopathic PAH (IPAH; n = 8), PAH associated with congenital heart disease (APAH-CHD; n = 7) or heritable PAH with one or more affected relatives (HPAH; n = 3).…”
Section: Patient Cohort and Clinical Assessmentmentioning
confidence: 99%
“…Best et al identified two additional mutations [ 52 ], and one additional mutation has been identified in Chinese pediatric PAH patients [ 53 ]. In 2020, a new mutation in KCNK3 was identified in a Dutch national cohort of children with PAH [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, 12 different KCNK3 mutations have been identified in 19 patients [ 11 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation